HLA Genotype of Patients with Severe Haemophilia A due to Intron 22 Inversion with and without Inhibitors of Factor VIII - Oldenburg, J; Picard, J K; Schwaab, R; Brackmann, H H; Tuddenham, E G D; Simpson, E (Thrombosis and Haemostasis, 1997)
Molecular genetic studies have shown that development of antibodies to factor VIII (inhibitors) occurs most frequently in patients with severe haemophilia due to major gene lesions including inversions, stop codons and large deletions. Previous studies of HLA type were performed on inhibitor and non-inhibitor patients with diverse uncharacterised mutations which may have confounded detection of significant associations. We therefore selected a group of patients with a single mutation type, the prevalent intron 22 inversion, with or without inhibitors, to determine HLA genotype. Seventy-one such patients, 42 without and 29 with inhibitors (13 high, 9 low and 7 transient responders) were genotyped for MHC Class I HLA-A, -B, -C and Class II HLA-DQA, -DQB and -DRB loci. No strong correlation of any HLA-allele to inhibitor or non-inhibitor status was found. However, alleles of the haplotype HLA-A3, HLA-B7, HLA-C7, HLA-DQA0102, HLA-DQB0602, HLA-DR15 occurred more often in inhibitor patients. Since the alleles of this extended haplotype are common in the North European population only a very strong association would achieve statistical significance. Further studies of groups of patients similar to those studied here will be needed to confirm or exclude this association.